1998
DOI: 10.1097/00001756-199802160-00025
|View full text |Cite
|
Sign up to set email alerts
|

Temporal constraints of auditory event synthesis

Abstract: The temporal constraints of auditory event synthesis were investigated using event-related potentials. Standard stimuli consisted of an initial constant-frequency segment followed by a frequency glide. Occasionally, stimuli deviating from this standard both in intensity and within the direction of the glide were presented in the otherwise repetitive sound sequence. Previous results suggested that such 'double' deviants elicit only a single mismatch negativity (MMN) if the two temporally separate deviant elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 8 publications
2
26
1
Order By: Relevance
“…The width of the temporal window of integration was evaluated by several studies on human MMN, e.g., 150 ∼ 170 ms (Yabe et al 1997), ∼ 200 ms (Winkler et al 1998), 200 ∼ 250 ms (Tervaniemi et al 1994). The authors determined the width of the temporal windows to be 300 ∼ 400 ms (Kanoh et al 2001), which was longer than that reported by other authors.…”
Section: Temporal Integrationmentioning
confidence: 98%
“…The width of the temporal window of integration was evaluated by several studies on human MMN, e.g., 150 ∼ 170 ms (Yabe et al 1997), ∼ 200 ms (Winkler et al 1998), 200 ∼ 250 ms (Tervaniemi et al 1994). The authors determined the width of the temporal windows to be 300 ∼ 400 ms (Kanoh et al 2001), which was longer than that reported by other authors.…”
Section: Temporal Integrationmentioning
confidence: 98%
“…For example, unidimensional MMNs for frequency and duration are additive when they occur at similar latencies (Levänen, Hari, McEvoy, & Sams, 1993), whereas they are subadditive when they are separated by $70 msec (Czigler & Winkler, 1996), which is very similar to the present latency difference between the ATT and SCG MMNs. When the latency difference is larger than 200 msec, then two individualized responses are recorded for bidimensional deviants (e.g., Winkler, Czigler, Jaramillo, Paavilainen, & Näätänen, 1998, for intensity and frequency glide direction). It is also possible that in the present data, there is a combination of the two effects (P3a superposition and MMN subadditivity for critical latency differences).…”
Section: Separate Processing Of Timbre Dimensions In Auditory Sensorymentioning
confidence: 99%
“…Relevant for the current study are the MMN results regarding the detection of violations of temporal regularities. The MMN has been elicited by occasional decreases and increases in stimulus duration (Näätänen et al 1989;Winkler et al, 1996), shortenings of the stimulus onset asynchrony (SOA; onset-to-onset interval) and the inter-stimulus interval (ISI; offset-to-onset interval; Nordby et al, 1988;Takegata et al, 2001), stimulus omissions (Yabe et al, 1997), and infrequent changes in the temporal structure of complex sounds (Grimm and Schröger, 2005;Winkler et al, 1998) and sound patterns (Müller and Schröger, 2007;Takegata et al, 2005;Winkler and Schröger, 1995). These studies provided evidence that the various temporal aspects of auditory stimulation are encoded in the memory underlying the MMN response and that the MMN is elicited by violations of temporal expectations (for a review, see Czigler et al, 2003).…”
Section: Introductionmentioning
confidence: 99%